Elements in Color: Finding Symbolic Meanings in the Haitian Flag - Thrasybule, Margarette Marie (Recent Trends in Arts and Social Studies Vol. 3, 2023)
The purpose of this qualitative study is to discover the underlying meanings and themes portrayed in the Haitian flag. The symbolic representation of the artifact will be explored to consider relevance and share knowledge on the topic. The ensign took shape over two centuries ago, making the accounts from witnesses impossible to verify or clarify; in addition, there are overwhelming difficulties nowadays in securing the booking of more recent subjects for interview. Therefore, this inquiry will be conducted by means of a detailed investigation that includes an in-depth observation of the Haitian flag as represented in various formats and a rigorous literature review that focuses on all the themes displayed in the Haitian flag. The literature and artifacts associated with Haiti’s history have puzzled its people for a long time. One historical symbol left open to interpretation is the Haitian flag although its aesthetic appeal is apparent to many. Ascertaining precise meanings from the flag's design is difficult due to the lack of available information and alteration of the original design by successive political administrations. This study is an attempt to decipher the hidden significance embedded in the Haitian flag and explore various themes represented in its colorful elements. The themes that are displayed in the Haitian flag are an exemplification of symbols that carry several important messages pertaining to order, discipline, unity, self-control, strength, opportunities for commerce, economic development, stability, wisdom, and health. The flag embodies the pride Haitian natives have in self-identifying with a culture rich in beauty and content. The artifact is a resourceful guide that elicits substantive lessons aimed at progress, nationalism, and governance. It is also a spatial-temporal ensign with positive connotations and an ongoing inspiration for the homeland.